(untitled) - Batchelor, John (1971)
The Ainu were once thought of as a "vanishing people", dispossessed and marginalized during the colonization of their homeland. However, these indigenous people of Northern Japan are now reasserting both their culture and their claim to be the most ancient of the Japanese races
Keywords: Ainu